A administração tributária dos municípios brasileiros: uma avaliação do desempenho da arrecadação - Tristão, José Américo Martelli (2003)
Evaluate the tax collection and proposes a typology for the way Brazilian municipalities perform with regard to taxation, and aims at helping in the understanding of the difficulties faced by the local authorities in levying taxes. The survey encompasses 4617 municipalities, grouped according to the importance of each tax within the total revenue. The groups have been obtained through the use of Cluster Analysis, a multivariate data analysis technique.